Effects of Systemic Propranolol Application on the New Bone Formation in Periimplant Guided Bone Regeneration - Gunes, Nedim; Gul, Mehmet; Dundar, Serkan; Artas, Gokhan; Kobat, Mehmet Ali; Tekin, Samet; Isayev, Abulfaz (Uab Stilus Optimus, 2021)
Objectives: The aim of this experimental animal study was to evaluate the effects of systemic propranolol on new bone formation in peri-implant bone defects. Material and Methods: Implant slots were created 4 mm long and 2.5 mm wide. After the titanium implants were placed in the sockets, 2 mm defects were created in the neck of the implants. Bone grafts were placed in these defects. Then the rats were randomly divided into three equal groups: control (n = 8), propranolol dose-1 (PRP-1) (n = 8), and propranolol dose-2 (PRP-2) (n = 8) groups. In the control group, the rats received no further treatment during the eight-week experimental period after the surgery. The rats in the PRP-1 and PRP-2 groups were given 5 mg/kg and 10 mg/kg propranolol, respectively, every three days for the eight-week experimental period after the surgery. At the end of the experimental period, the rats were euthanized. Blood serum was collected for biochemical analysis, and the implants and surrounding bone tissues were used for the histological analysis. Results: There were no significant differences in the histological analysis results and the biochemical parameters (alkaline phosphatase, calcium, creatinine and phosphorus) of the groups (P > 0.05). Also, in the test groups, there was numerically but not statistically more new bone formation detected compared with the controls. Conclusions: Within the limitations of this study, propranolol did not affect the new bone formation in peri-implant defects.
Keywords: bone; peri-implantitis; propranolol; regeneration